2017
DOI: 10.2147/hp.s127042
|View full text |Cite
|
Sign up to set email alerts
|

Update on hypoxia-inducible factors and hydroxylases in oxygen regulatory pathways: from physiology to therapeutics

Abstract: The “Hypoxia Nantes 2016” organized its second conference dedicated to the field of hypoxia research. This conference focused on “the role of hypoxia under physiological conditions as well as in cancer” and took place in Nantes, France, in October 6–7, 2016. The main objective of this conference was to bring together a large group of scientists from different spheres of hypoxia. Recent advances were presented and discussed around different topics: genomics, physiology, musculoskeletal, stem cells, microenviron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 75 publications
0
20
0
1
Order By: Relevance
“…96 Hypoxia-induced factor-1 alpha (HIF1A) is a master transcriptional regulator of cellular response to hypoxia. 98,99 Thus, we hypothesized that apical hypoxia in GuMI culture would induce hypoxia-related responses in colon epithelia and promote epithelial barrier functions. First, we found under hypoxic conditions HIF1A gene expression was significantly increased (p = 0.0001) in GuMI-NB compared with Static cells cultured in normoxia, with a fold change of 1.52 (Figure 4a and 4b).…”
Section: Gumi Recapitulates Cell Responses To Hypoxiamentioning
confidence: 99%
“…96 Hypoxia-induced factor-1 alpha (HIF1A) is a master transcriptional regulator of cellular response to hypoxia. 98,99 Thus, we hypothesized that apical hypoxia in GuMI culture would induce hypoxia-related responses in colon epithelia and promote epithelial barrier functions. First, we found under hypoxic conditions HIF1A gene expression was significantly increased (p = 0.0001) in GuMI-NB compared with Static cells cultured in normoxia, with a fold change of 1.52 (Figure 4a and 4b).…”
Section: Gumi Recapitulates Cell Responses To Hypoxiamentioning
confidence: 99%
“…Such toxicityi sd ue to its micellar properties, involving the presence of hydrophobic alkyl chains and cationic nitrogens that are polar.O ne way to eliminate such toxicityi nvolves replacing CH 2 groups by oxygen atoms that are buried deep in the long heptylc hains. [116] The study by Ali et al demonstrated that the Mn 3 + mesotetrakis (N-methylpyridinium-2-yl) porphyrin (MnTM-2-PyP) reduced diabetes-induced oxidative stress and extended the lifespan of STZ diabetic rats if administered during the onset of diabetes. The presence of these oxygens,t ogether with the high lipophilicity confer excellent chemical and physical properties to Mn 3 + meso-tetrakis(N-n-butoxyethylpyridinium-2-yl)porphyrin, MnTnBuOE-2-PyP 5 + (MnBuOE, BMX-001).…”
Section: Manganese Porphyrinsmentioning
confidence: 99%
“…; Ratcliffe et al . ). In recent work, we have observed that general inactivation of HIF‐2α, but not HIF‐1α, ablates the proliferation that occurs within days of exposure to hypoxia in adult mice (Hodson et al .…”
Section: Introductionmentioning
confidence: 97%